Numerical study of vented hydrogen explosions in a small scale obstructed chamber. (23rd August 2018) - Li, Ruipengyu; Malalasekera, Weeratunge; Ibrahim, Salah
Abstract: There is a growing need to understand and estimate the explosion hazards associated with hydrogen storage and utilisation. This paper presents a comprehensive numerical study on the explosion characteristics of a lean hydrogen-air mixture in a small-scale obstructed vented chamber. The large eddy simulation (LES) technique is employed to study the highly unsteady turbulence-driven explosion when the flame propagates past successive obstructions. A dynamic flame surface density (DFSD) model is applied to the filtered chemical source term in the LES to account for the progressive wrinkling of the deflagrating flame. The driving mechanism of pressure rise and the underlying physics of flame-obstacle interactions are illustrated using the detailed LES results. The paper considers 11 individual flow experimental configurations of various obstacle number, size and location. They are further classified into six groups to investigate the influence of the level of blockage and the separation distance between adjacent obstructions. Critical safety-related parameters including the maximum overpressure and its incidence time are analysed. A comparison with propane is also made to highlight the substantial overpressure and flame acceleration of hydrogen deflagrations. Satisfactory agreements have been obtained between the LES and the experimental data, and this confirms the capability of the developed computational models in capturing essential explosion features and information for the study of vented hydrogen explosions. Graphical abstract: Image 1 Highlights: Characteristics of vented hydrogen explosions in a range of obstacle configurations. A dynamic combustion model to account for the various level of flame wrinkling. Greater overpressure and higher sensitivity to obstructions compared with propane. Influence of the number, location and size of the obstacles.